Is Bacillus amyloliquefaciens inoculation effective for the enhancement of soil and plant nutrient status and fruit quality of Solanum lycopersicum L. in the presence of composted organic fertilisers?. Issue 2 (28th January 2023) - Bouček, Jiří; Kulhánek, Martin; Košnář, Zdeněk; Podhorecká, Klára; Obergruber, Michal; Hönig, Vladimír; Száková, Jiřina; Beesley, Luke; Berchová Bímová, Kateřina; Omara-Ojungu, Carol; Hlavsa, Tomáš; Trakal, Lukáš
ABSTRACT: The impacts of plant-associated Bacillus amyloliquefaciens, strain FZB42 RhizoVital 42® (RV) on the yield and macronutrient content of tomato plants was investigated in a pot trial in a low-nutrient soil with and without the addition of compost and vermicompost amendments composed of mixtures of cow manure, vegetation and wastepaper. Plant uptake of N, P, K, Ca, Mg, S was compared among the treatments, whilst the saccharide contents in the tomato fruits were also determined. Vermicompost applications increased soil nutrient bioaccessibility resulting in higher contents of S and P in plants grown in vermicompost, compared to compost. In particular, the content of sulphur in roots for the two vermicompost variants was 2.5-fold higher than for compost treatments due to increased soil bioaccessibility impacted by earthworm bioturbation. The yield of aboveground biomass increased significantly after the addition of compost with or without RV. Moreover, RV significantly enhanced Ca, K and Mg uptake into roots (and shoots) after vermicompost application, and saccharide contents in the tomato fruits enhanced in the compost amended soil. In summary, this study indicates that the inoculation of tomato plants with B. amyloliquefaciens impacts favourably on fruit quality, especially when soil is amended with composted organic fertiliser